2018
DOI: 10.1097/jom.0000000000001215
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Chemical Sensitivity

Abstract: Objective:Systematic bibliography analysis of about the last 17 years on multiple chemical sensitivity (MCS) was carried out in order to detect new diagnostic and epidemiological evidence. The MCS is a complex syndrome that manifests as a result of exposure to a low level of various common contaminants. The etiology, diagnosis, and treatment are still debated among researchers.Method:Querying PubMed, Web of Science, Scopus, Cochrane library, both using some specific MESH terms combined with MESH subheadings an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 84 publications
(233 reference statements)
0
33
0
Order By: Relevance
“…One of the main problems in defining MCS based on its clinical presentation is the variation in individual responses to chemicals, which is mutable to the point that a characteristic pattern of symptoms has not been yet established [ 2 ]. The most common MCS symptoms reported in the literature are headache, dizziness, seizures, heart arrhythmia, gastrointestinal problems, breathing difficulties, fatigue, lethargy, sore throat, hyperosmia, dyspnoea, confusion, difficulty concentrating, and asthma attacks [ 5 , 37 ]. Patients usually refer these symptoms to different organs and systems and relate them to exposure or contact with one or more chemicals [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main problems in defining MCS based on its clinical presentation is the variation in individual responses to chemicals, which is mutable to the point that a characteristic pattern of symptoms has not been yet established [ 2 ]. The most common MCS symptoms reported in the literature are headache, dizziness, seizures, heart arrhythmia, gastrointestinal problems, breathing difficulties, fatigue, lethargy, sore throat, hyperosmia, dyspnoea, confusion, difficulty concentrating, and asthma attacks [ 5 , 37 ]. Patients usually refer these symptoms to different organs and systems and relate them to exposure or contact with one or more chemicals [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…MCS patients related such reactions to exposure to such different chemicals as solvents, hydrocarbons, organophosphates, and heavy metals. MCS is currently included in the wider spectrum of idiopathic environmental intolerance (IEI), which also considers physical stimuli such as electromagnetic fields [ 5 ]. Common MCS symptoms are hyperosmia, weakness, lethargy, sore throat, dyspnoea, headache, and difficulties in concentration [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the effect of age on CI is unclear, the prevalence of CI in persons ≥ 60 years of age is lower than that in other age groups [ 2 , 4 ] and the prevalence of CI in teenagers is much lower than that in adults [ 20 ]. In addition, the importance of genetic factors involved in xenobiotic metabolism in CI etiology is still uncertain concerning the importance of genetic variability as opposed to epigenetic mutation [ 16 , 21 ]. Although the underlying mechanisms between asthma/allergy and CI may be different, several studies reported comorbidity and multimorbidity between these conditions [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many factors can trigger sensitivity to chemicals. Besides genetic factors, drug/chemical exposure-related increased sensitivity to common chemicals may possibly occur by a variety of mechanisms including brain alterations and neurogenic inflammation/kindling [ 37 42 ], immune alterations [ 37 39 , 41 ], stimulation of the nitrogen oxide/peroxynitrate pathway [ 43 ], and damage/irritation to the respiratory tract [ 41 , 44 ]. Additional testing of the patient for toxicology/biochemical data (such as measurement of activity of various P450 enzymes, measurement of metabolites, inflammation and oxidative damage) might elucidate the biochemical pathways involved with his adverse reactions to drugs and chemicals.…”
Section: Discussionmentioning
confidence: 99%